QOL-08. NEUROPSYCHOLOGICAL ASSESSMENT OF 21 PATIENTS TREATED FOR A CHILDHOOD BRAIN FRONTAL LOBE TUMOUR: ASPECTS OF SOCIAL COGNITION AND THEORY OF MIND. Issue 2 (22nd June 2018) - Longaud, Audrey; Chevignard, Mathilde; Grill, Jacques; Dufour, Christelle; Puget, Stéphanie; Sainte-Rose, Christian; Valteau-Couanet, Dominique; Dellatolas, George
Abstract: BACKGROUND: Frontal lobe function is often evaluated with diffuse lesions such as traumatic brain injury, frontal lobe epilepsy. Few cases study has been reported, evaluating frontal lobe dysfunction after focal lesions, such as tumoral lesions. OBJECTIVES: The aim of the study was to evaluate social cognition and theory of mind performances in 21 patients treated for benign or malignant frontal lobe tumours in childhood. To our knowledge; no study to date has directly measured social cognition aspects and theory of mind aspects in frontal benign or malignant lobe tumours in children and adolescents. 1st ans 2nd order false-belief tests of theory of mind tests (Sally & Ann test, Smarties), facial expression recognition, motor imitation tests were performed. METHODS: 21 patients (mean age at the time of evaluation: 14.3 years old, mean age at the end of treatments: 9.3 years-old) treated for frontal benign (n=4)/malignant (n=17) lobe tumour during childhood were included in our study. A comparison group of 42 patients were matched on gender, age and level education. RESULTS: Whereas statistical analysis of our study revealed no theory of mind disturbances in 1st and 2 nd order false belief in our population, specific measures were identified as discriminating the most patients from controls, such as facial expression recognition test and motor imitation tests. The role and impact of neurons mirrors in our population is discussed.